ANALYSIS OF PEDESTRIAN PATH WIDTH REQUIREMENTS IN THE MANUKAN LOR ROAD AREA, SURABAYA CITY - Habib Yoga Kusuma; Kurnia Hadi Putra; Theresia Maria Chandra Agusdini (Journal Innovation of Civil Engineering (JICE), 2024)
The commercial area on Manukan Lor street is one of the places in the city of Surabaya that currently has quite heavy traffic. The problem in this area is that there is no special pedestrian/pedestrian route available so it can endanger pedestrians, apart from that it can also disrupt the activity of traffic vehicles. The aim of this thesis refers to the formulation of the problem and the existing background, including: Determining the characteristics of pedestrians in the Manukan Lor Street area of Surabaya, determining the width requirements for pedestrian/pedestrian lanes in the Manukan Lor Street area, and to determine the performance results in Manukan Lor road section after and before the sidewalk. Guidelines used in planning pedestrian paths in the area "Sidewalk Planning Guidebook Number.007/T/BNKT/1990 Directorate General of Highways", "Guidebook for Building Construction Materials and Civil Engineering Ministry of PUPR Number.02/SE/M/2018 regarding technical planning of pedestrian facilities", and "Indonesian Road Capacity Guidebook 2023 (PKJI 2023)". The results of the analysis of the required width of the pedestrian path on the Manukan Lor road are 1.5 m wide with the level of service obtained is category A, and includes low-level side obstacles, with an average increase in the degree of saturation (Dj) of 0.026 but still in service level category C with a stable flow the speed can be controlled by traffic.  Keywords: Pedestrian Width; Characteristics; Road Performance.